THE POWER OF RED SHOOT LEAF EXTRACT: HOW SOLVENT VARIATIONS AFFECT BONE HEALING AFTER TOOTH EXTRACTION IN RATS - Ika Rachmawati; Risyandi Anwar; Megawati Prajarini; Salma Mei Asti; Ita Febriyani (Universitas Muhammadiyah Semarang, 2025)
Background: A popular medicinal plant in Indonesia, red shoot leaves (Syzygium myrtifolium Walp) have been extensively explored for their biological activity and potential to promote hard tissue healing in tooth sockets after extraction. However, few studies have examined this potential. Analyzing the impact of red leaf extract with different solvents on alveolar bone repair in the post-extraction socket in Wistar rats was the aim of this investigation.Method: This study aimed to determine differences in the healing process of bone after tooth extraction. Conducted on 15 male Wistar rats (12 weeks old, weighing 150 – 200 grams). The experiment includes three groups: Group A (5 animals received a gel base as a negative control group), Group B: (5 animals received 2% n-hexane gel treatment of red shoot leaves) and Group C (5 animals received 2% extract ethanol gel of red shoot leaves, based on designated observation days 30. The assessment involves bone remodeling area o from radiograph.Outcome: The average alveolar bone density varies greatly, as indicated by the study's p value of 0.000 (p < 0.005). The group that had 2% n-hexane gel treatment for red shoot leaves had the highest average alveolar bone density. According to the results of the phytochemical screening test, the n-hexane extract included triterpenoid and steroids, but the ethanol extract contained flavonoids, tannins, and alkaloids. The findings of this study demonstrate that the use of solvents with varying polarity can have an impact on bone remodeling.Conclusion: The alveolar bone mineral density of Wistar rats following tooth extraction was increased by 2% n-hexane gel treatment of red shoot leaves.